Are policies in Vietnam conducive of healthy food environments? Insights from a multi-sectoral policy landscape analysis - Even, Brice; Truong Thi, Trang. Thu; Nguyen, Thu Duong; Thai, Hang Thi Minh; Pham Thi, Huong Mai; Bui Thi, Viet Anh; Nguyen, Tuan Linh; Bene, Christophe (2023)
Current food systems fail to address the triple burden of malnutrition — undernutrition, micronutrient deficiencies, and overnutrition (Popkin, 2019; Béné, 2019; Fanzo, 2020). The Food and Agriculture Organization (FAO) reports that approximately 462 million people worldwide are underweight, while 1.9 billion adults (39%) are overweight or obese. In 2020, globally, 149 million children under the age of five were stunted, 45 million were wasted, and 38.9 million were overweight or obese (FAO, 2021).